THE EVOLUTION OF ENGLISH AS A GLOBAL LANGUAGE (INGLIZ TILINING GLOBAL TILGA AYLANISHI) - Fayzullayeva Ruxsora Jamoldinovna; Hamidov Nodirbek (TADQIQOTLAR, 2025)
Abstract: This article explores the transformation of the English language from a  regional  dialect  into  a  global  lingua  franca.  By  examining  historical,  political, economic,  and  technological  factors,  the  study  outlines  the  reasons  for  English’s widespread  use  today.  It  also  addresses  challenges  associated  with  linguistic dominance, such as cultural erosion and language endangerment. The research reflects on how English shapes identity, communication, and global relations in the modern era.